An Empirical Study of the Relations Between Drug Abuse and Delinquency Among Adolescents - Otero-Lopez, Jose Manuel; Luengo-Martin, Angeles; Miron-Redondo, Lourdes; Carrillo-de-la Peña, Maria Teresa; Romero-Triñanes, Estrella (The British journal of criminology, 1994)
This paper further explores the drug-delinquency relationship. Three hypotheses present in the literature are examined: (1) drug abuse causes delinquency; (2) delinquency causes drug abuse; and (3) there is no causal relationship between drug abuse and delinquency, and other variables are responsible for the statistical relationship. The sample of this study comprised 2,022 male students between 14 and 18 years of age. The results of the statistical analyses performed (frequencies, correlation, and regression) support the third hypothesis and confirm the existence of a group of variables (family, peer, and personality) that influence both drug abuse and delinquent behaviour